A new technique for the radiolabelling of mixed leukocytes with zirconium‐89 for inflammation imaging with positron emission tomography. (8th April 2016) - Fairclough, M.; Prenant, C.; Ellis, B.; Boutin, H.; McMahon, A.; Brown, G.; Locatelli, P.; Jones, A.K.P.
Abstract : Mixed leukocyte (white blood cells [WBCs]) trafficking using positron emission tomography (PET) is receiving growing interest to diagnose and monitor inflammatory conditions. PET, a high sensitivity molecular imaging technique, allows precise quantification of the signal produced from radiolabelled moieties. We have evaluated a new method for radiolabelling WBCs with either zirconium‐89 ( 89 Zr) or copper‐64 ( 64 Cu) for PET imaging. Chitosan nanoparticles (CNs) were produced by a process of ionotropic gelation and used to deliver radiometals into WBCs. Experiments were carried out using mixed WBCs freshly isolated from whole human blood. WBCs radiolabelling efficiency was higher with [ 89 Zr]‐loaded CN (76.8 ± 9.6% ( n  = 12)) than with [ 64 Cu]‐loaded CN (26.3 ± 7.0 % ( n  = 7)). [ 89 Zr]‐WBCs showed an initial loss of 28.4 ± 5.8% ( n  = 2) of the radioactivity after 2 h. This loss was then followed by a plateau as 89 Zr remains stable in the cells. [ 64 Cu]‐WBCs showed a loss of 85 ± 6% ( n  = 3) of the radioactivity after 1 h, which increased to 96 ± 6% ( n  = 3) loss after 3 h. WBC labelling with [ 89 Zr]‐loaded CN showed a fast kinetic of leukocyte association, high labelling efficiency and a relatively good retention of the radioactivity. This method using 89 Zr has a potential application for PET imaging of inflammation. Abstract : Mixed leukocyte (white blood cells) trafficking using positron emission tomography (PET) is receiving growing interest to diagnose and monitor inflammatory conditions. PET, a high sensitivity molecular imaging technique, allows precise quantification of the signal produced from radiolabelled moieties. We have evaluated a new method for radiolabelling WBCs with either zirconium‐89 ( 89 Zr) or copper‐64 ( 64 Cu) for PET imaging.